Adjusting team involvement: a grounded theory study of challenges in utilizing a surgical safety checklist as experienced by nurses in the operating room - Wæhle Hilde; Haugen Arvid; Søfteland Eirik; Hjälmhult Esther (BMC Nursing, 2012)
Abstract Background Even though the use of perioperative checklists have resulted in significant reduction in postoperative mortality and morbidity, as well as improvements of important information communication, the utilization of checklists seems to vary, and perceived barriers are likely to influence compliance. In this grounded theory study we aimed to explore the challenges and strategies of performing the WHO’s Safe Surgical Checklist as experienced by the nurses appointed as checklist coordinators. Methods Grounded theory was used in gathering and analyzing data from observations of the checklist used in the operating room, in conjunction with single and focus group interviews. A purposeful sample of 14 nurse-anesthetists and operating room nurses as surgical team members in a tertiary teaching hospital participated in the study. Results The nurses’ main concern regarding checklist utilization was identified as “how to obtain professional and social acceptance within the team”. The emergent grounded theory of “adjusting team involvement” consisted of three strategies; distancing, moderating and engaging team involvement. The use of these strategies explains how they resolved their challenges. Each strategy had corresponding conditions and consequences, determining checklist compliance, and how the checklist was used. Conclusion Even though nurses seem to have a loyal attitude towards the WHO’s checklist regarding their task work, they adjusted their surgical team involvement according to practical, social and professional conditions in their work environment. This might have resulted in the incomplete use of the checklist and therefore a low compliance rate. Findings also emphasized the importance of: a) management support when implementing WHO’s Safe Surgical Checklist, and b) interprofessional education approach to local adaptation of the checklists use.